What is the incidence of methotrexate or leflunomide discontinuation related to cytopenia, liver enzyme elevation or kidney function decline?. (16th March 2021) - Nakafero, Georgina; Grainge, Matthew J; Card, Tim; Mallen, Christian D; Zhang, Weiya; Doherty, Michael; Taal, Maarten W; Aithal, Guruprasad P; Abhishek, Abhishek
Abstract: Objectives: To examine incidence of treatment changes due to abnormal blood-test results and, to explore rates of treatment changes due to liver, kidney and haematological blood-test abnormalities in autoimmune rheumatic diseases (AIRD) treated with low-dose MTX or LEF. Methods: Data for people with AIRDs prescribed MTX or LEF were extracted from the Clinical Practice Research Datalink. Participants were followed-up from first prescription of MTX or LEF in primary care. Primary outcome of interest was drug discontinuation, defined as a prescription gap of ≥90 days following an abnormal (or severely abnormal) blood-test result. Dose reduction was examined between consecutive prescriptions. Incidence rates per 1000 person-years were calculated. Results: 15,  670 and 2, 689 participants contributing 46,  571 and 4, 558 person-years follow-up were included in MTX and LEF cohorts, respectively. The incidence of MTX and LEF discontinuation with abnormal (severely abnormal) blood-test was 42.24 (6.16) and 106.53 (9.42)/1000 person-years in year 1, and 22.44 (2.84) and 31.69 (4.40)/1000 person years, respectively, thereafter. The cumulative incidence of MTX and LEF discontinuation with abnormal (severely abnormal) blood tests was 1 in 24 (1 in 169), 1 in 9 (1 in 106) at 1 year; and 1 in 45 (1 in 352), 1 in 32 (1 in 227) per-year, respectively, thereafter. Raised liver enzymes were the commonest abnormality associated with drug discontinuation. MTX and LEF dose reduction incidence were comparable in year 1, however, thereafter MTX dose was reduced more often than LEF [16.60 (95% CI 13.05, 21.13) vs 8.10 (95% CI 4.97, 13.20)/1000 person-years]. Conclusion: MTX and LEF were discontinued for blood-test abnormalities after year 1 of treatment, however, discontinuations for severely abnormal results were uncommon.